Multi-omics Comparative Analysis of Streptomyces Mutants Obtained by Iterative Atmosphere and Room-Temperature Plasma Mutagenesis - Liu, Tan; Huang, Zhiyong; Gui, Xi; Xiang, Wei; Jin, Yubo; Chen, Jun; Zhao, Jing (Frontiers in Microbiology, 2021)
Sponges are the most primitive multicellular animals, which contain a large number of unique microbial communities. Sponge-associated microorganisms, especially actinomyces, have the potential to produce diverse active natural products. However, a large number of silent secondary metabolic gene clusters have failed to be revived under laboratory culture conditions. In this study, iterative atmosphere and room-temperature plasma (ARTP) mutagenesis coupled with multi-omics conjoint analysis was adopted to activate the inactive wild Streptomyces strain. The desirable exposure time employed in this study was 75 s to obtain the appropriate lethality rate (94%) and mutation positive rate (40.94%). After three iterations of ARTP mutagenesis, the mutants with antibacterial activities significantly increased by 75%. Transcriptome analysis showed that the differential gene expression levels of encoding type I lasso peptide aborycin had a significant upward trend in active mutants compared with wild strains, which was confirmed by the LC-MS results with a relative molecular mass of 1082.43 ([M + 2H]2+ at m/z = 2164.86). Moreover, metabolome comparative analysis of the mutant and wild strains showed that 4 spectra or mass peaks presented obvious differences in terms of the total ion count or extracting ion current profiles, and each peak corresponded to a specific compound exhibiting moderate antibacterial activity against gram-positive indicators. In general, our data showed that the ARTP treatment method coupled with the multi-omics profiling analysis could be used to estimate the valid active molecules of metabolites from microbial crudes without a time-consuming isolation process.